Analisis faktor resistensi karyawan terhadap penggunaan HRIS menggunakan innovation resistance theory - Ketut Ayu Anggi Pradnyaswari; Adrian Wijanarko (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2026)
This study examines how factors within Innovation Resistance Theory (IRT)—namely usage barrier, value barrier, risk barrier, tradition barrier, and image barrier—affect employee resistance to the use of Human Resource Information System (HRIS) in companies located in Jakarta. Research discussing employee resistance toward HRIS implementation using the IRT framework remains limited in the Indonesian context. A quantitative approach was employed using a survey method, with data collected from 200 employees who have experience using HRIS through purposive sampling. The data were gathered using a Likert-scale questionnaired and analyzed through multiple linear regression with the help of SPSS software. The findings reveal that all five factors significantly contribute to employee resistance. Among them, risk barrier emerges as the most influential factor, indicating that concerns related to data security and system uncertainty play a central role in shaping employees’ reluctance to adopt HRIS. These results suggest that organization need to place greater emphasis on building trust and ensuring system reliability when implementing new technologies. This study contributes to the development of IRT application in the context of HRIS usage. Overall, this study provides both theoretical and practical contribution by enriching the discussion on innovation resistance and offering insights for organizations in effectively managing employee resistance to support successful HRIS implementation.